EFFECT OF FEEDBACK IN FORMATIVE ASSESSMENT IN THE STUDENT LEARNING ACTIVITIES ON CHEMICAL COURSE TO THE FORMATION OF HABITS OF MIND - Nahadi, N.; Firman, H.; Farina, J. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
The aim of this study was to find the impact of feedback in formative assessment in the learning process activity and students learning outcomes on learning chemistry. The method used on this study was quasi experiment research with non-equivalent control group design. The result showed that the application of feedback in formative assessment has a positive impact toward students learning process activity. Students become more enthusiastic, motivated, and more active on the learning process. Thus in this study can be conclude that feedback in formative assessment have a positive impact toward the learning process activity to form a habits of mind.